The IMRD overflow phenomenon: form and function of Japanese-language journal documents - Rodrigo M. L. de Aragão (Revista de Lingüística y Lenguas Aplicadas)
Despite the growing body of research on the overall organization of documents from academic journals, little is known about the use of IMRD-based structures—the pattern composed of Introduction, Methods, Results, and Discussion sections and its variants—in publication categories other than the research article. The current paper addresses this phenomenon with the focus on Japanese-language journal documents. Both the structure and the basic function of 186 documents in Japanese of five categories different from the research article were analyzed. It was found that IMRD-based structures are consistently used in two and sparsely used in one of the five categories. Additionally, it was found that most documents exhibiting these structures report some kind of investigation. The results point to a close connection between form and function; the overflow of IMRD-based structures seems to be an external sign of the advance in academic journals of publication categories centered on research processes.